HrQoL in hair loss‐affected patients with alopecia areata, androgenetic alopecia and telogen effluvium: the role of personality traits and psychosocial anxiety. (2nd December 2018) - Russo, P.M.; Fino, E.; Mancini, C.; Mazzetti, M.; Starace, M.; Piraccini, B.M.
Abstract: Background: Illness impact on HrQoL has been widely studied in hair loss‐affected patients, yet no study has addressed whether individual differences modulate HrQoL in patients with alopecia areata (AA), androgenetic alopecia (AGA) and telogen effluvium (TE). Objective: To identify the personality dimensions most predictive of the impact of disease on HrQoL. Method: A single‐site cross‐sectional study was carried out in the Dermatology Unit of Sant'Orsola‐Malpighi Hospital, Bologna between September 2016 and September 2017. The study included 143 patients (105 females, ages 18–60 years) diagnosed with AA ( n = 27), AGA ( n = 80) and TE ( n = 36). Illness severity, alopecia type, age, gender, education and civil status were documented. Health‐related quality of life (HrQoL), personality traits, trait anxiety, emotional intelligence, social anxiety and social phobia were also measured. Results: AA, AGA and TE groups differed significantly for illness severity with most severe patients falling in AA type. For HrQoL, Gender × Group interaction resulted significant with AGA females reporting a higher impact of hair loss on quality of life than males, while TE males were more impacted by hair loss than AA and AGA males. Lower scores were obtained by AGA females than males on emotional intelligence while no significant differences were evidenced on other groups. A significant Gender × Group interaction was also found for trait anxiety, social phobia and social anxiety: consistently, AGA females reported higher scores than AGA males in all three measures. Finally, discriminant analysis evidenced that anxiety‐related traits can contribute to reliably predict hair loss impact on HrQoL, regardless of illness severity and alopecia type. Conclusions: We recommend that gender and individual differences in anxiety‐related dimensions be considered as key factors in gaining a deeper understanding of hair loss impact on quality of life as well as in reducing the burden of illness in alopecia‐affected patients.